The dislocation unpinning from stoppers in KBr single crystals сaused by elastic stresses and temperature - Petchenko, О.M.; Petchenko, G.О.; Boiko, S.M.; Litvinenko, A.S.; Kоlyada, O.Yu. (Вопросы атомной науки и техники, 2019)
The impulse echo-method was applied to study, in the temperature range 300…435 K and at 7.5 MHz frequency, the dislocation attenuation αd(σ) in KBr crystals as a function of static loading in the quasi-elastic strain range. It has been found that the temperature increase at stresses σ < σy (σy is the yield limit of a crystal) leads to the intensive dislocations’ unpinning. Consequently, concentration of stoppers, controlling their motion, sharply decreases and the effective length of oscillating dislocation segments increases. As a result of experimental data processing the energy of the impurity atom binding with dislocation U₀ was calculated in the following work. За допомогою імпульсного ехо-методу на частоті 7,5 МГц у температурному інтервалі 300…435 К вивчено дислокаційне згасання ультразвуку αd(σ) у KBr як функція статичного навантаження в квазіпружній області деформацій. Визначено, що підвищення температури при величинах σ < σy (σy – границя плину кристалів) призводить до інтенсивного відкріплення дислокацій. Внаслідок цього концентрація стопорів, що контролюють їх рух, різко знижується, а ефективна довжина дислокаційного сегмента збільшується. Шляхом обробки експериментальних результатів розраховано величину енергії зв’язку U₀ домішкового атома з дислокацією. С помощью импульсного эхо-метода на частоте 7,5 МГц в температурном интервале 300…435 К изучено дислокационное затухание ультразвука αd(σ) в KBr как функция статического напряжения в квазиупругой области деформаций. Определено, что повышение температуры при величинах σ < σy (σy – предел текучести кристаллов) приводит к интенсивному откреплению дислокаций. Из-за этого концентрация стопоров, ограничивающих их движение, резко снижается, а эффективная длина дислокационного сегмента увеличивается. Путем обработки экспериментальных результатов рассчитана величина энергии связи U₀ примесного атома с дислокацией.